HABITAT PREFERENSIAL TARSIUS BELITUNG (Cephalopachus bancanus saltator Elliot, 1910) - Fitriana, Fifin; Prasetyo, Lilik Budi; Kartono, Agus Priyono (Media Konservasi, 2016)
Belitung tarsier (Cephalopachus bancanus saltator) is an endemic species in Belitung Island from Cephalopachus genus. Existence of belitung tarsier in its habitat is now under threatened by deforestatition. Due to lack information about its habitat and as conservation effort, this research was tackled to reveal the characteristic of habitat preference of belitung tarsier. The aim of this study are to identify characteristic of habitat preference of belitung tarsier. This research was conducted in March until May 2016 at around Mount Tajam Protected Forest and plantation area. Presence of tarsiers were identified by direct observation, urine odor detection, identifying based tarsier habitat suitability and the local information. Chi-square and Neu methode was used to analyze the variable of habitat preference of belitung tarsiers. This research found that characteristics of habitat preference of belitung tarsier consisted of its homerange was prefer to dry land agricultural and shurb land cover type, not too tight canopy cover (Leaf Area Index /LAI value of 0,83-2,46), close to the edge of forest (0 -874 m), roads (0 – 3.698 m) and settlements (0-403 m), elevation range was between 1 -142 m asl, slope slightly (0-15%), temperature 24-25 0C and high rainfall (3.222 – 3.229 mm/year). Characteristic of habitat preference information could be considered to develop conservation action of belitung tarsier. Keywords: belitung tarsiers, habitat, habitat preference, tarsier